2019
DOI: 10.17981/ingecuc.15.2.2019.06
|View full text |Cite
|
Sign up to set email alerts
|

Metodología para la caracterización geotécnica de suelos tropicales derivados de rocas volcánicas

Abstract: Introducción- Los suelos que se encuentran en zonas tropicales, al estar sometidos a factores que favorecen el proceso de meteorización química, tienden a presentar propiedades geotécnicas particulares frente a los que se encuentran en zonas templadas. Aspectos primordiales como el grado de meteorización y génesis del material, que tienden a influenciar las propiedades del suelo, no son tomados en cuenta por las metodologías que pretenden estudiar las características de dichos suelos. En consecuencia, son insu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
(8 reference statements)
1
1
0
Order By: Relevance
“…The friction angle was similar for horizons H-1 and H-2 (38° and 41°) and decreased to 30° for horizon H-3. These friction angles are very high, compared to the friction angle of lateritic clays derived from amphibolite (φ=10º) (Fresneda-Saldarriaga et al, 2013) and the residual soils of the Antioquian Batholith (φ = 23º) (Romaña et al, 2009), and similar to the values reported for other lateritic soils with friction angles between 28º -39º (Suárez, 1998).…”
Section: Unsaturated-undrained Shear Strength and Stressstrain Behaviorsupporting
confidence: 76%
See 1 more Smart Citation
“…The friction angle was similar for horizons H-1 and H-2 (38° and 41°) and decreased to 30° for horizon H-3. These friction angles are very high, compared to the friction angle of lateritic clays derived from amphibolite (φ=10º) (Fresneda-Saldarriaga et al, 2013) and the residual soils of the Antioquian Batholith (φ = 23º) (Romaña et al, 2009), and similar to the values reported for other lateritic soils with friction angles between 28º -39º (Suárez, 1998).…”
Section: Unsaturated-undrained Shear Strength and Stressstrain Behaviorsupporting
confidence: 76%
“…In Medellín, several studies of mineralogical and physical characterization of soils derived from other geological formations have been carried out, such as those on residual soils of the Antioquian Batholith (Romaña et al, 2009) and lateritic soils derived from amphibolite (Fresneda-Saldarriaga et al, 2013), however, no study was reported on the soils derived from dunite. This article presents the results of the mineralogical characterization of residual soil from "Medellín Dunite" and its relationships with the physical properties and unsaturated undrained shear strength.…”
Section: Introductionmentioning
confidence: 99%